2022
DOI: 10.1002/ehf2.13853
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial pressure represents cumulative cardiac burden in heart failure with preserved ejection fraction

Abstract: AimsRight‐sided filling pressure is elevated in some patients with heart failure (HF) and preserved ejection fraction (HFpEF). We hypothesized that right atrial pressure (RAP) would represent the cumulative burden of abnormalities in the left heart, pulmonary vasculature, and the right heart.Methods and resultsEchocardiography was performed in 399 patients with HFpEF. RAP was estimated from inferior vena cava morphology and its respiratory change [estimated right atrial pressure (eRAP)], and patients were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Secondary PH and pulmonary vascular disease may enhance right ventricular afterload, subsequently contributing to right ventricular dysfunction and remodeling, leading to a further increase in RAP [ 14 , 15 ]. Previous studies have demonstrated that RAP could represent the cumulative cardiac burden in HFpEF [ 16 , 17 ], and higher RAP is independently associated with adverse outcomes in HFpEF [ 17 , 18 ]. Therefore, compared with CPO, CPO RAP integrates an additional risk factor and could better identify patients with predominantly right ventricular or biventricular involvement, which could be an explanation for the better prognostic performance for adverse outcomes of CPO RAP than CPO.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary PH and pulmonary vascular disease may enhance right ventricular afterload, subsequently contributing to right ventricular dysfunction and remodeling, leading to a further increase in RAP [ 14 , 15 ]. Previous studies have demonstrated that RAP could represent the cumulative cardiac burden in HFpEF [ 16 , 17 ], and higher RAP is independently associated with adverse outcomes in HFpEF [ 17 , 18 ]. Therefore, compared with CPO, CPO RAP integrates an additional risk factor and could better identify patients with predominantly right ventricular or biventricular involvement, which could be an explanation for the better prognostic performance for adverse outcomes of CPO RAP than CPO.…”
Section: Discussionmentioning
confidence: 99%
“…5 RAP has been shown to be of prognostic significance in patients with chronic or acute left HF, but its implications in right-sided HF remain contentious. 6,7 The recent advent of transcatheter tricuspid valve interventions (TTVI) has not only provided safe and effective means to reduce TR but also offers a model for studying right-sided HF by partly attenuating its haemodynamic basis. 5 Initial observations in patients with TR-associated right-sided HF have reported reductions in RAP following TTVI, but they found no significant associations .…”
Section: Introductionmentioning
confidence: 99%
“…These pressures are quantified by right atrial pressures (RAP), which are linked to central venous congestion 5 . RAP has been shown to be of prognostic significance in patients with chronic or acute left HF, but its implications in right‐sided HF remain contentious 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…As a chronic, progressive disease, the accumulated burdens on the body over time result in frequent rehospitalisation for those diagnosed with HF, with 25% likely to be re-admitted after 30 days, and 50% likely to be re-admitted within 6 months, with a large percentage of these being avoidable [ 7 , 8 ]. Elevated central venous pressure (CVP) has been associated with rehospitalised patients both when presenting at the hospital [ 9 ], as well as the increase in time-integrated pressure out of hospital [ 10 ], suggesting this may be used as a marker for early intervention, reducing rehospitalisations [ 11 ]. Development of an at-home, non-invasive measurement of this pressure may be beneficial in this domain, as some individuals have shown interest in the use of mobile health applications to manage their own symptoms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%